Layer-specific strain in patients with cardiac amyloidosis using tissue tracking MR - Li, Zheng; Yan, Cheng; Hu, Guo-Xiang; Zhao, Rui; Jin, Hang; Yun, Hong; Wei, Zheng; Pan, Cui-Zhen; Shu, Xian-Hong; Zeng, Meng-Su (Frontiers in Radiology, 2023)
Background Cardiac infiltration is the major predictor of poor prognosis in patients with systemic amyloidosis, thus it becomes of great importance to evaluate cardiac involvement. Purpose We aimed to evaluate left ventricular myocardial deformation alteration in patients with cardiac amyloidosis (CA) using layer-specific tissue tracking MR. Material and Methods Thirty-nine patients with CA were enrolled. Thirty-nine normal controls were also recruited. Layer-specific tissue tracking analysis was done based on cine MR images. Results Compared with the control group, a significant reduction in LV whole layer strain values (GLS, GCS, and GRS) and layer-specific strain values was found in patients with CA (all P < 0.01). In addition, GRS and GLS, as well as subendocardial and subepicardial GLS, GRS, and GCS, were all diminished in patients with CA and reduced LVEF, when compared to those with preserved or mid-range LVEF (all P < 0.05). GCS showed the largest AUC (0.9952, P = 0.0001) with a sensitivity of 93.1% and specificity of 90% to predict reduced LVEF (<40%). Moreover, GCS was the only independent predictor of LV systolic dysfunction (Odds Ratio: 3.30, 95% CI:1.341–8.12, and P = 0.009). Conclusion Layer-specific tissue tracking MR could be a useful method to assess left ventricular myocardial deformation in patients with CA.